Liberal feminist values as reflected in Leo Tolstoy's Anna Karenina - Fajarani, Septian Tri (Universitas Ahmad Dahlan, 2021)
This research is entitled Liberal Feminist Values As Reflected In Leo Tolstoy's Anna Karenina. This novel described a woman who broke her wedding because she wants to feel the love. Through Anna Karenina, she fought for her rights to express her opinion to her husband. The purpose of this study is to describe the characteristics of the main character and feminist characteristics of the main character in the novel. Qualitative method is applied in this research. The main data source in this study is Leo Tolstoy's novel Anna Karenina and to complete the data source, this research also uses other books, reviews of novels, films and sources from the internet. The method of data analysis in this study is qualitative method. In this study, a feminist approach from Rosamarie Tong and